Pengaruh Sifat Materialisme dan Kecanduan Internet Terhadap Perilaku Pembelian Impulsif Secara Online - Winatha, Regina Giovanna; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 3 No 3 (2014), 2014)
This study was conducted to determine the influence of materialism and internet addiction on online impulse buying behavior. Number of samples of this study was 140 respondents who have been through certain criteria. Based on the regression analysis and Moderate Regression Analysis (MRA),each of materialism and internet addiction significantly has positive effect on online impulsive buying behavior, but materialism are not shown to act as a moderating the relationship between internet addiction and online impulse buying behavior. Online marketers in Indonesia are advised to shows more the benefits of the product by promoting the emotional element, so that consumers feel their ownership of the product will make it happier and look better. Marketers can use social media to spread information as well as interact with consumers, so that consumers can easily get information about existing products and promotions.
Keywords: materialism, internet addiction, impulse buying, internet